(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Fatty liver disease, fibrosis, and cirrhosis represent a spectrum of liver conditions that pose significant health risks globally. Accurate diagnosis and staging of these conditions are crucial for effective management and intervention. Among the various imaging modalities used, high-resolution ultrasonography (HRUS), computed tomography (CT), and magnetic resonance imaging (MRI) are commonly employed. Objectives: The primary objective of this study is to assess and compare the diagnostic accuracy of HRUS, CT, and MRI in identifying fatty liver, fibrosis, and cirrhosis. A secondary objective is to explore the association between clinical factors such as body mass index (BMI), age, and the prevalence of liver diseases. Methods: This is a cross-sectional study conducted over a four-month period at two clinics: Awami Clinic Manthar and Al-sehat Clinic Sadiqabad. A total of 150 patients referred for abdominal ultrasound due to suspected liver disease were included. Inclusion criteria were adults aged 18 or older, diagnosed with fatty liver, fibrosis, or cirrhosis, while pregnant women and individuals with significant comorbidities were excluded. Imaging was performed using HRUS, CT, and MRI, and clinical data, including BMI, age, and medical history, were collected. Statistical analysis was performed using SPSS software, with the chi-square test and t-test applied to analyze associations and differences between groups. Results: Of the 150 participants, 85 (56.7%) had fatty liver, 40 (26.7%) had fibrosis, and 25 (16.6%) had cirrhosis. A statistically significant association was found between high BMI and the presence of fatty liver. HRUS demonstrated high sensitivity (80%) in detecting fatty liver but had lower accuracy in staging fibrosis and cirrhosis. MRI, on the other hand, showed superior accuracy in staging liver fibrosis and cirrhosis, with sensitivity and specificity rates of 92% and 89%, respectively. CT provided moderate diagnostic accuracy but was less effective compared to MRI, especially in fibrosis staging. Conclusion: It is concluded that HRUS is a valuable screening tool for fatty liver disease, while MRI should be the preferred modality for assessing advanced liver conditions like fibrosis and cirrhosis. A combination of imaging techniques, along with clinical factors such as BMI, should be used for a comprehensive approach to liver disease diagnosis.